Implementasi strategi human capital (HC) pada Pusdiklat Penanggulangan Kebakaran dan Penyelamatan Provinsi DKI Jakarta - Yuliastini, Dewi; Haryanto, Arie; Djuanita, Maharani Kinanti; Hamdi, Edi; Negoro, Dimas Angga (Journal of Management and Digital Business, 2024)
Human capital is a crucial element within organizations that reflects their individual competencies, which include knowledge, expertise, ability, and skill. This study aims to analyze the human capital strategies implemented by Pusdiklat Penanggulangan Kebakaran dan Penyelamatan Provinsi DKI Jakarta, which is striving for autonomy as a Regional Public Service Agency (BLUD). This study employs a qualitative approach with descriptive methods to systematically and accurately depict various phenomena related to the implementation of human capital strategies. The research results indicate that this Training and Education Center is still in the Grow and Build stage, so the main focus of the human capital strategy is on improving the competence and quality of human resources. Several strategies implemented include the development of E-Learning or Learning Management Systems (LMS), engaging and effective internal training programs, and external training such as seminars, workshops, and continuing education. Additionally, recruitment strategies, strengthening organizational culture, and career development are also essential parts of supporting the enhancement of human resource competencies.